Impact of Internet Banking on the Financial Performance of Indonesian Banking - Nuralya, Firda Ulfah; Putri, Sherly Cheisa; Leon, Farah Margaretha (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This research aims to identify variables that influence bank performance in banking companies listed on the Indonesia Stock Exchange. The addition of the capital adequacy ratio variable as an independent variable is a novel part of this research. This research method includes collecting data from 22 banking companies over a five year period (2019-2023) with a total of 110 data that meet the criteria by applying data processing analysis using panel data regression analysis techniques. The results of this research show that (1) The internet banking variable has a positive and significant influence on financial performance. (2) The loan to deposit ratio variable has no significant effect on financial performance. (3) The bank size variable has a positive and significant effect on banking return on assets (4) The capital adequacy ratio variable has no significant effect on banking return on assets.